2013
DOI: 10.2139/ssrn.2373242
|View full text |Cite
|
Sign up to set email alerts
|

The National Health Insurance Scheme in Ghana: Implementation Challenges and Proposed Solutions

Abstract: The International Food Policy Research Institute (IFPRI), established in 1975, provides evidence-based policy solutions to sustainably end hunger and malnutrition and reduce poverty. The Institute conducts research, communicates results, optimizes partnerships, and builds capacity to ensure sustainable food production, promote healthy food systems, improve markets and trade, transform agriculture, build resilience, and strengthen institutions and governance. Gender is considered in all of the Institute's work.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Individuals are expected to pay an annual premium to enable them receive health care at no cost. The scheme also exempts older population above age 70 and children under age 18 as well as pregnant women from paying premium (Gajate-Garrido and Owusua, 2013). This may explain the low average household spending on health in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals are expected to pay an annual premium to enable them receive health care at no cost. The scheme also exempts older population above age 70 and children under age 18 as well as pregnant women from paying premium (Gajate-Garrido and Owusua, 2013). This may explain the low average household spending on health in the country.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with Mishra et al study in Nepal where they posited that SHI revenue collection in large informal sectors is a major economic challenge to successful implementation. 4 It is also an indication that the scheme survives largely on the health insurance levy of 2.5% tax on goods and services, accounting for about 70% of revenues 28 ; making sustainability a challenge as it has not been increased in spite of the growth in membership. The low level of contributions and what was seen as poorly targeted exemptions were argued to be a threat to sustainability, which has been noted as a major challenge in large informal economies.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of implementation challenges of the NHIS in Ghana have also identified politicisation as a major challenge resulting in people not joining the scheme because they either associate the scheme with a political party or a particular politician in office. 28 Added to this is the rapidity with which policy decisions are made as implementation progresses. Indeed, as suggested by an earlier study, the lack of policy clarity and frequent changes in the policy made the scheme confusing to potential members, 28 thereby undermining enrolment and renewals and hence the finances of the scheme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations